The language of literature and the metamorphosis of humanity - Lazić, Nebojša J. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The German philosopher Martin Heidegger and the Serbian poet Vladislav Petković Dis differ in culture, language, vocation and, finallz, in the views they had about the overall human reasoning and creativity. In this paper, the author tries to demonstrate that the creative personality of the Serbian poet—in the author’s opinion, a poet not recognized at his true value—fits in the profile of poetry defined by Heidegger when he writes about „poor times”. The poetic language of Dis is not always unified, however, his poetry is the closest to the purpose of every art: the revelation of the meaning of creation and existence. Heidegger, in his philosophy, Vladislav Petković, in his poetry, both show that reflection and writing are in harmony and even have the same purpose—the discovery of the essential truth.